The Development of Biology Module Based on Emotional Spiritual Quotient in Evolution Topic for Senior High School - Fatma Rahmadhani; Armen Armen; Rahmawati Darussyamsu; Muhyiatul Fadilah; Dwi Hilda Putri (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
This study aims to produce a valid biology module based on emotional spiritual quotient (ESQ) in an evolution topic for senior high school students grade XII. This conducted research used the Plomp development method. In this model, there were three steps established, such as; preliminary research, developing or prototype phase, and assessment phase. For implementation validity, the research subjects were a biology teacher and five biology lecturers. The instrumentation used were; interview questionnaire, self-evaluation sheet, and validity questionnaire. The obtained data analyzed by qualitative and quantitative methods. From the research, yield a new biology module with ESQ based in evolution lesson for senior high school students grade XII. Based on the expert review, obtained the score of validity 3.71 which indicated very valid criteria.